Role of bronchial washing in the diagnosis of endoscopically visible lung cancer - Liwsrisakun C. (2014)
Objective: To evaluate the usefulness of bronchial washings in addition to endobronchial biopsies and/or bronchial brushings for the pathological diagnosis of endoscopically visible lung cancer. Material and Method: A retrospective study of patients diagnosed as lung cancer by bronchoscopy between January 1995 and December 1998. Patients were included in the study if they had 1) endoscopically visible tumors (exophytic mass or irregular mucosa) and 2) bronchial washings (BWs) performed together with either endobronchial biopsies (EBBs) or bronchial brushings (BRs). Patients were classified into 3 groups according to the result of the histocytology as follows: A) positive in both BWs and EBBs/BRs, B) positive in only EBBs/BRs and C) positive in only BWs. A number of patients in each group were analyzed to see the benefit of BWs as an add-on diagnostic tool. The authors also evaluated the benefits of BWs in the subgroup of patients who had necrotic and bleeding tumor. Statistical analysis of the data was performed by using the likelihood-ratio chi-square test. Results: Two hundred and twenty-two patients were included in the present study. The number of patients in group A, B and C was 108, 108, and 6, respectively. Therefore, BWs was the only diagnostic procedure in 6 patients (2.7%). Those 6 patients all had incurable non-small cell lung cancer. The likelihood of a positive BW s in an exophytic mass was no different from irregular mucosa. The likelihood of a positive BWs in a tumor with necrosis was higher than in a tumor without necrosis. In contrast, tumors with active bleeding had a lower likelihood of positive BWs when compared with those without bleeding. The likelihood ratio showed no statistical significance in any of the groups. Conclusion: The addition of BWs to either EBBs or BRs is beneficial, but it may not be cost-effective. This procedure may be useful in patients with an endoscopically visible necrotic tumor. In contrast, the bronchoscopic finding of a bleeding tumor may be a negative predictor. This procedure may be a suitable approach when performed only in selected cases, such as necrotic tumor or negative initial EBB s/BRs.